Morphological and molecular diversification of slender salamanders (Caudata: Plethodontidae: Batrachoseps) in the southern Sierra Nevada of California with descriptions of two new species - Jockusch, Elizabeth L.; Martínez-Solano, Iñigo; Hansen, Robert W.; Wake, David B. (Zootaxa, 2012)
Slender salamanders of the genus Batrachoseps achieve relatively high diversity in the Kern Canyon region at the southernend of the Sierra Nevada of California through high turnover of species with small geographic ranges. The status of severalpopulations of Batrachoseps in this region is enigmatic, and both morphological and molecular data have suggested thatsome populations do not belong to any of the currently recognized species. Identification of species in this region is com-plicated by the apparent extinction of Batrachoseps relictus in the vicinity of its type locality in the Lower Kern RiverCanyon. Here we analyze a comprehensive morphological dataset to evaluate diversity in the Kern River Canyon region.We conclude that populations from Breckenridge Mountain are conspecific with B. relictus, while populations from northof the Kern River previously treated as B. relictus belong to an undescribed species. The morphological data also showthe distinctiveness of populations from the Upper Kern River Canyon. Thus, we describe two new species, Batrachosepsbramei sp. nov. for populations from the Upper Kern River Canyon and Batrachoseps altasierrae sp. nov. for populationsfrom the southern Sierra Nevada previously referred to B. relictus. B. bramei sp. nov. and B. relictus are members of thenigriventris group; B. altasierrae sp. nov. belongs to the group formerly called the relictus group, which we rename thediabolicus group. We conclude by presenting allozyme and mitochondrial DNA sequence data that support the distinctiveness of these newly described species and provide a hypothesis of relationships within the nigriventris group.